HUBUNGAN WAKTU TUNGGU PELAYANAN RESEP TERHADAP KEPUASAN PASIEN DI APOTEK MITRA SEHAT BANJARBARU: The Relationship Of Waiting Time For Prescription Services With Patient Satisfaction At Mitra Sehat Pharmacy Banjarbaru - Mursidatul Jannah; Yulistia Budianti Soemarie; Hasniah Hasniah (Politeknik Unggulan Kalimantan, 2025)
Wait time for prescription services is a critical indicator of the efficiency and effectiveness of pharmacy staff in processing, preparing, and dispensing medications to patients. The faster and more accurate the service process, the more it demonstrates optimal workflow and coordination within the pharmacy service unit. This study aims to determine the relationship between waiting time and patient satisfaction for prescription services at the Mitra Sehat Banjarbaru Pharmacy for the period October - November 2024. This research was conducted using quantitative research methods through a cross-sectional study design. The instrument used was a questionnaire adopted from a Likert scale with SERVQUAL dimensions. The questionnaire was distributed to respondents who received prescription services at the Mitra Sehat Banjarbaru pharmacy for the period 15 October – 15 November 2024. Based on the research results, the waiting time for prescription services was 75.2% in accordance with the expected standards. , and 24.8% did not match. Respondent satisfaction was 59.4% moderate satisfaction, 29.7% very satisfied and 10.9% less satisfied. The SPSS statistical test results show that there is a significant relationship between waiting time and respondent satisfaction (p < 0.05).